The concept of "Mobile sky" - Остроумов, І.В. (Proceedings of National Aviation University (archive), 2009)
The navigation and control for light aviation based on mobile communication service in the bottom airspace have been proposed. The main principles of “Mobile sky” conception have been formulated and grounded. In the paper have been represented the main advantages for use this conception in Ukraine.